Temporal evolution of the permanent shadowed regions at Mercury poles: applications for spectral detection of ices by SIMBIOSYS-VIHI on BepiColombo mission. Issue 1 (26th August 2020) - Filacchione, Gianrico; Frigeri, Alessandro; Raponi, Andrea; Ciarniello, Mauro; Capaccioni, Fabrizio; De Sanctis, Maria Cristina; Carli, Cristian; Galluzzi, Valentina; Cremonese, Gabriele; Lucchetti, Alice; Re, Cristina; Massironi, Matteo
ABSTRACT: Radar observations from the Earth and multi-instrument measurements by MESSENGER mission have indicated the presence of large quantities of ices within the permanent shadowed regions (PSRs) located at Mercury poles. The detection and mapping of the distribution of volatile species on PSRs are among the primary scientific goals of the Spectrometer and IMagers for MPO Bepicolombo Integrated Observatory SYStem (SIMBIO-SYS) suite aboard ESA's BepiColombo mission. We report about a three-steps preparatory study mainly focusing on SIMBIO-SYS/Visible and near Infrared Hyperspectral Imager (VIHI) 0.4–2.0 μ m imaging spectrometer aiming (1) to render the solar illumination temporal evolution occurring on polar regions and in particular on Prokofiev and Kandinsky craters by studying the effects of shadows and penumbras caused by the finite apparent solar disc; (2) to simulate the spectral reflectance of various mixtures of average Mercury terrain and water ice in the spectral range of the VIHI imaging spectrometer channel in direct illumination, penumbra and shadowed illumination conditions; and (3) to verify the resulting VIHI signal-to-noise ratio during the different phases of the BepiColombo mission.